Coefficient estimates in new subclasses of analytic and bi-univalent functions defined by the combinations of the q-derivative and the Sǎlǎgean derivative operator - Orhan, Halit (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.53 We introduce and study two new subclasses of the function class Σ of bi-univalent functions defined in the open unit disk and associated with the Sǎlǎgean and q-derivative operators. Furthermore, we find estimates for the Taylor–Maclaurin coefficients |a_2| and |a_3| of the functions from these new subclasses. The accumulated results are quite interesting and new.